1979
DOI: 10.1136/thx.34.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole and surgery in bronchial carcinoma patients: increase in deaths from cardiorespiratory failure.

Abstract: Life table analysis of early entry to this randomised blind trial of 318 patients has shown a significantly poorer survival for resected lung cancer patients treated with levamisole for three days before operation and three days a fortnight thereafter than for placebo-treated controls. This excess was largely due to deaths that had been attributed to operation or other causes (non-cancer deaths), most occurring in the six weeks after operation. In the 99 resected patients treated with levamisole there was a 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the other study, Anthony and colleagues adjusted the dose to body weight and found no difference between the levamisole and control groups. 7 This 49 study actually showed an increase in deaths due to cardiorespiratory disease in the patients treated with levamisole.…”
Section: Levamisole Therapy Of Lung Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…In the other study, Anthony and colleagues adjusted the dose to body weight and found no difference between the levamisole and control groups. 7 This 49 study actually showed an increase in deaths due to cardiorespiratory disease in the patients treated with levamisole.…”
Section: Levamisole Therapy Of Lung Cancermentioning
confidence: 94%
“…In the study by Anthony and associates there were an inordinate number of cardiorespiratory deaths in patients treated with levamisole. 7 However, an extensive effort in Europe and the United States to confirm toxicity of the agent failed to confirm these findings. 6 Willoughby and Wood reviewed a variety of side effects of levamisole and found that treatment had been stopped in less than 5 percent of patients because of adverse reactions.…”
Section: Complications Of Levamisolementioning
confidence: 99%
“…Palliative Rh-negative patients showed a similar effect. Differential response to immunotherapy by blood group could have implications for the interpretation of immunotherapy trials.We have reported that excess post-operative deaths in levamisole-treated lung cancer patients were more frequent in patients who were blood group 0 and/or Rh (D)-negative [3]. The excess deaths were due to cardiorespiratory failure and were associated (in the only cases where serum samples were available for testing) with the presence of antimyocardial antibodies that were not detected in any patient without the syndrome.…”
mentioning
confidence: 86%
“…Analyses performed excluding noncancer deaths from both groups showed no advantage or disadvantage from levamisole. 2 Work in animal tumor models suggests that direct intralesional BCG followed by resection of the tumor and regional lymph nodes will provide systemic antitumor immunity capable of eradicating artificially induced metastatic disease. The in-vestigation of Holmes, which included twenty-seven patients who had resection of the tumor, two to four weeks following percutaneous intralesional injection of BCG, showed 85 percent of the lung cancer patients and 58 percent of the group with pulmonary metastasis alive and well at a median followup time for the series of sixteen months.…”
Section: Immunotherapymentioning
confidence: 99%